2020
DOI: 10.5334/gh.532
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability, HIV and the Risk of Cardiovascular Diseases in Rural South Africa

Abstract: Background: Antiretroviral therapy (ART) transformed human immunodeficiency virus (HIV) infection into a chronic disease. Possible HIV-associated complications have emerged including cardiovascular diseases (CVD). Objectives: This study aims to determine the heart rate variability (HRV) distribution and association between HRV and HIV treated with ART in a rural African population. Methods: This cross-sectional study included 325 participants of the Ndlovu Cohort Study, South Africa. HRV was measured using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…The variables of baroreflex sensitivity and HRV in patients with hepatitis C virus were also found to be lower than those in healthy patients ( Osztovits et al, 2009 ). In a cross-sectional study included 325 participants, HIV-infected participants had lower HRV than HIV-uninfected participant ( Godijk et al, 2020 ). Moreover, previous studies have shown that HRV alters in the presence of systemic infection, and HRV monitoring may enhance the diagnosis and prognosis of infection, and HRV may help evaluate risk of deterioration in patients with sepsis and merits validation and further evaluation ( Ahmad et al, 2009 ; Barnaby et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The variables of baroreflex sensitivity and HRV in patients with hepatitis C virus were also found to be lower than those in healthy patients ( Osztovits et al, 2009 ). In a cross-sectional study included 325 participants, HIV-infected participants had lower HRV than HIV-uninfected participant ( Godijk et al, 2020 ). Moreover, previous studies have shown that HRV alters in the presence of systemic infection, and HRV monitoring may enhance the diagnosis and prognosis of infection, and HRV may help evaluate risk of deterioration in patients with sepsis and merits validation and further evaluation ( Ahmad et al, 2009 ; Barnaby et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, attempting to summarize, one study reported the occurrence of a parasympathetic predominance [36], another one a parasympathetic withdrawal [35], another study did not find differences in HRV parameters between non-critically ill COVID-19 patients and healthy controls [31], while two studies found a complex misalignment of ANS [37,41], involving both parasympathetic and sympathetic branches. Therefore, HRV parameters are strongly influenced by demographic factors, such gender and age [97], which varied widely among the included studies, and they could be altered by several clinical conditions [97][98][99], such as infectious diseases themselves [12,[100][101][102].…”
Section: Discussionmentioning
confidence: 99%
“…(2011) found a lower RMSSD in HIV-infected patients on ART, which was related to a longer exposure to PI’s regimens and dyslipidemia [ 33 ]. Moreover, imbalance in linear parameters in time and frequency domains has been demonstrated in several studies in HIV-infected patients on ART regimens containing PI’s [ 15 , 29 , 36 , 37 , 53 , 55 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Godjik & Cols. (2020) observed that HIV-infected patients on ART is an independent risk factor for cardiovascular disease [ 58 ].…”
Section: Discussionmentioning
confidence: 99%